2017
DOI: 10.1021/acs.oprd.7b00230
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Practical Enzymatic Process for Preparation of (S)-2-Chloro-1-(3,4-difluorophenyl)ethanol

Abstract: (S)-2-Chloro-1-(3,4-difluorophenyl)­ethanol (1) is a vital chiral intermediate for the synthesis of Ticagreloran effective treatment for acute coronary syndromes. A ketoreductase (KRED) KR-01 in our KRED library was screened to transform 2-chloro-1-(3,4-difluorophenyl)­ethanone (2) into the chiral alcohol 1. During process optimization, the bioreduction procedure was performed at a substrate concentration of 500 g/L, giving a near 100% conversion with >99.9% ee. The product 1 was directly obtained by extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 27 publications
0
32
0
2
Order By: Relevance
“…The biphasic mixture of product and starting material was separated, and the organic material recirculated to increase the conversion. The asymmetric reduction of the chloroethyl precursor 27 was also reported, in this case using a ketoreductase from a metagenomic library . The process for the synthesis of alcohol 28 was optimized to give up to 500 g/L substrate concentration.…”
Section: Enabling Technologymentioning
confidence: 99%
“…The biphasic mixture of product and starting material was separated, and the organic material recirculated to increase the conversion. The asymmetric reduction of the chloroethyl precursor 27 was also reported, in this case using a ketoreductase from a metagenomic library . The process for the synthesis of alcohol 28 was optimized to give up to 500 g/L substrate concentration.…”
Section: Enabling Technologymentioning
confidence: 99%
“…Examples of WC biocatalytic processes. (a) Select scaffolds accessed through WC biocatalytic reactions (Baker Dockrey et al., ; Guo et al., ; Hadi et al., ; Kaluzna et al., ; Matsuyama et al., ; Milker et al., ; Xie & Tang, ). (b) WC biocatalysis utilizing a multi‐enzyme cascade to generate chiral benzylic amines (Both et al., ) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%
“…On an industrial scale, several processes have been designed to employ WC biocatalysts. Notably, WC biocatalysis has been utilized for the generation of valuable chemical feedstocks such as enantio‐enriched alcohols, (Matsuyama, Yamamoto, & Kobayashi, ) performance material monomers, (Kaluzna et al., ) and pharmaceutically relevant intermediates, (Guo et al., ) as well as the late‐stage functionalization of active pharmaceutical ingredients during route development (Figure a; Guo et al., ; Milker, Fink, Rudroff, & Mihovilovic, ; Xie & Tang, ). Recently, researchers at GlaxoSmithKline demonstrated that a WC biocatalysis platform is also useful for discovery of new synthetic routes on the gram‐scale, developing several biocatalytic routes to chiral 1,3‐substituted cyclohexanones, such as 2 (Hadi et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations